Influence of Tunneling in Cohesionless Soil for Different Tunnel Geometry and Volume Loss under Greenfield Condition - Raja Kanagaraju; Premalatha Krishnamurthy (Advances in Civil Engineering, 2020)
This paper presents the numerical analysis of settlement to profile the vulnerable zone or influence zone due to tunneling activities in cohesionless deposits for free field or Greenfield conditions. The analysis considers the factors like saturated density (γsat), unsaturated density (γunsat), angle of shearing resistance (φ), deformation modulus (ES), volume loss (VL), and the support pressure of the shield head at the tunnel face. The obtained results using a finite element program (FEM) PLAXIS 3D are compared with measured and predicted surface settlement using field measuring instruments, and analytical and empirical solution show a reasonable agreement and are found to be conservative. From literature, for Greenfield condition the ground settlement equal to 10 mm is taken as the minimum value to map the influencing zone considering the fact that the structure which lies beyond this zone would undergo negligible settlement. Settlement trough and 10 mm settlement contour characteristics are presented for different tunnel sizes placed at the same depth and the same tunnel size placed at different depths, respectively. Various influencing zones are arrived for the sandy grounds of different denseness based on the parametrical studies involving parameters such as tunnel size “D,” tunnel axis depth “z,” and volume loss “VL.”